2021
DOI: 10.3390/ma14237479
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Optimization of Dimensional Accuracy and Porosity of High Impact Polystyrene Material Printed by FDM Process: PSO, JAYA, Rao, and Bald Eagle Search Algorithms

Abstract: High impact polystyrene (HIPS) material is widely used for low-strength structural applications. To ensure proper function, dimensional accuracy and porosity are at the forefront of industrial relevance. The dimensional accuracy cylindricity error (CE) and porosity of printed parts are influenced mainly by the control variables (layer thickness, shell thickness, infill density, print speed of the fused deposition modeling (FDM) process). In this study, a central composite design (CCD) matrix was used to perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…HIPS was selected due to its versatility, economical nature, and impact resistance properties (Table 1). It is known for being easy to fabricate and machine, making it a suitable choice for this study [15]. HIPS is preferred for low-strength structural applications, readily available, and relatively cheap.…”
Section: Methodsmentioning
confidence: 99%
“…HIPS was selected due to its versatility, economical nature, and impact resistance properties (Table 1). It is known for being easy to fabricate and machine, making it a suitable choice for this study [15]. HIPS is preferred for low-strength structural applications, readily available, and relatively cheap.…”
Section: Methodsmentioning
confidence: 99%
“…It is moderately priced, easily molded and machinable [ 23 ]. High Impact Polystyrene (HIPS), Polyethylene terephthalate glycol (PETG) and Polylactic acid (PLA): Materials typically used for 3D printing using the Fused Deposition Modeling process (FDM) [ 24 , 25 ]. FDM process can be used to fabricate complex geometries or internal structures and has been widely applied in many industries, such as the aerospace industry [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…High Impact Polystyrene (HIPS), Polyethylene terephthalate glycol (PETG) and Polylactic acid (PLA): Materials typically used for 3D printing using the Fused Deposition Modeling process (FDM) [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that all approaches performed similarly and provided optimal settings. Various other studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] have explored the optimization of process parameters in additive manufacturing using hybrid approaches. These studies utilized various intelligent algorithms to attain optimal results for specific objectives related to their respective problems.…”
Section: Introductionmentioning
confidence: 99%